Keutuhan Membran Spermatozoa Disekuensing Sentrifugasi Gradien Densitas Percoll Berpengencer Andromed dan CEP-2 yang Ditambahkan Kuning Telur (MEMBRANE INTACT OF SPERMATOZOA FOLLOWING SEXING USING PERCOLL DENSITY GRADIENT CENTRIFUGATION IN ANDROMED AND C - Diliyana, Yudha Fika; Susilawati, Trinil; Rahayu, Sri (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
The aim of this study was to observe the best extender in protecting the membrane of bovine spermatozoafollowing sexing by percoll density gradient centrifugation. Freshly collected semen were obtained fromBalai Besar Inseminasi Buatan Singosari-Malang. The semen were diluted in andromed and CaudalEpididymal Plasma-2 (CEP-2) added with 10% egg yolk extenders.The sperm membrane integrity wasobserved using Hypo-osmotic Swelling Test (HOST). Sperm capacitation and acrososome reaction wereassessed using Chlortetracycline Fluorescence Assay.The results showed that andromed and CEP-2 addedwith 10% egg yolk were able to retain the sperm membrane integrity, whereas sperm capacitation andacrosome reaction were kept low. Caudal Epididymal Plasma-2 (CEP-2) added with 10% egg yolk seemedto give better protection towards the sperm membrane intact in comparison to andromed extender.
Keywords: andromed, Caudal Epididymal Plasma-2, sexing, spem membrane